EFEKTIVITAS PENGGUNAAN TEPUNG MAGGOT BLACK SOLDIER FLY (BSF) SEBAGAI SUBSTITUSI SEBAGIAN RANSUM KOMERSIAL TERHADAP KUALITAS FISIK TELUR PUYUH PETELUR: EFFECTIVENESS OF USING BLACK SOLDIER FLY (BSF) MAGGOT FLOUR AS A PARTIAL SUBSTITUTION FOR COMMERCIAL RATIONS ON THE PHYSICAL QUALITY OF LAYING QUAIL EGGS - Ali, Dharru Indira Tirtomas; Wulandari, Eudia Christina; Abdurrahman, Zakaria Husein (Universitas Boyolali, 2025)
This study aims to evaluate the effectiveness of Black Soldier Fly (BSF) maggot meal as a partial substitute for commercial feed on the physical quality of quail eggs (Coturnix coturnix japonica). A total of 100 female quails were used and housed in 20 cage partitions, each containing five birds. A Completely Randomized Design (CRD) was employed with four treatment levels of maggot meal inclusion (0%, 5%, 10%, and 15%) and five replications. The feed composition was formulated using the iso-protein principle to ensure equal protein content across all treatments. Observed parameters included yolk index, albumen index, Haugh Unit, egg weight, shell weight, and shell thickness. The results showed that the 10% maggot meal treatment produced the highest yolk index, indicating that the protein and fat ratio at this level best supported yolk formation. However, the highest albumen index and Haugh Unit were found in the control group without maggot meal, suggesting that standard commercial feed more effectively maintains albumen quality. The highest egg weight, shell weight, and shell thickness were recorded in the group fed with 5% maggot meal, identifying this level as the most optimal in supporting egg mass and shell integrity. Overall, it can be concluded that supplementing quail diets with 5% BSF maggot meal yields the most favorable effect on egg physical quality without significantly compromising internal egg components.